RISKS TO THE CONTINUITY OF THE INVESTMENT PROJECT IN CONSTRUCTION - T. Yu. Shemyakina; E. S. Kotova (Вестник университета)
The international standards and state standard specifications of the Russian Federation of business continuity management have been analyzed. Process of assessment of maturity level of the construction organization in the field of business continuity and its increase by definition of strategy, stabilization, renewal and complete recovery of activity, decrease in influence and reduction of consequences has been investigated. Modern threats to the continuity for the companies at the global level, typical risks of the investment and construction project have been considered. The best international practices of business continuity management, the plan of business continuity which can be applied at implementation of investment and construction projects, have been offered.